ANALYSIS OF JUDGE'S DECISION THAT WAS OUT OF THE CRIME OF MURDER - Syamsul Haling; Andi Taufik (JILPR Journal Indonesia Law and Policy Review, 2022)
The research method used in writing the results of this thesis research is normative juridical. The aims of this study are: (1) To find out and analyze the qualifications of corporations as subjects of corruption. (2) To find out and analyze the form of criminal liability against corporations as perpetrators of criminal acts of corruption. (2) To know the verdict of the judge who is free from the crime of murder. The results of the study show (1) In relation to the analysis of the judge's decision that is free from the crime of murder, it is clear that, to determine whether an act is included in a criminal act, a sharp analysis is needed from a judge without overriding the applicable law. (2) Seeing the obstacles faced by judges in determining decisions that are independent of the provisions of the Act on the crime of murder, then every judge who has convened should have matured emotionally, in terms of the thoughts, attitudes and authority of the judge himself and who is not inferior. What is important is the ability of mature human resources.